2023
DOI: 10.33022/ijcs.v12i4.3266
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Artificial Intelligence in Education: Opportunities, Challenges, Threats and Obstacles. A Literature Review.

Indra Saputra,
Murni Astuti,
Muhammad Sayuti
et al.

Abstract: The research background is the rapid development of AI which affects various aspects of education. The purpose of this study is to analyze in depth about the opportunities, challenges, threats and obstacles to the implementation of AI in education. The research method used in this study is semy-systematic literature review. The analysis technique used is a meta-narrative approach that includes the process of identifying, analyzing, recognizing patterns and topic-related themes. The results describe that AI opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…The findings in this study indicate that the implementation of AI-integrated TBPj has a high impact on improving undergraduate student meta-skills, which is in line with several previous reports that examined almost the same learning design. Several previous studies have reported that the use of AI has had a positive impact on teacher management in managing learning administration; for example, planning and assessing learning and providing innovative media and teaching materials according to student needs (Cardona et al, 2023;Igbokwe, 2023;Saputra et al, 2023;Sok & Heng, 2023;Zawacki-Richter et al, 2019). Moreover, the application of AI in learning equips prospective teachers with the ability to adapt to technological advancements as a means of creatively addressing learning challenges (Chen et al, 2020;Heeg & Avraamidou, 2023;Zhai et al, 2021).…”
Section: ▪ Results and Disscussionmentioning
confidence: 99%
“…The findings in this study indicate that the implementation of AI-integrated TBPj has a high impact on improving undergraduate student meta-skills, which is in line with several previous reports that examined almost the same learning design. Several previous studies have reported that the use of AI has had a positive impact on teacher management in managing learning administration; for example, planning and assessing learning and providing innovative media and teaching materials according to student needs (Cardona et al, 2023;Igbokwe, 2023;Saputra et al, 2023;Sok & Heng, 2023;Zawacki-Richter et al, 2019). Moreover, the application of AI in learning equips prospective teachers with the ability to adapt to technological advancements as a means of creatively addressing learning challenges (Chen et al, 2020;Heeg & Avraamidou, 2023;Zhai et al, 2021).…”
Section: ▪ Results and Disscussionmentioning
confidence: 99%
“…En un contexto donde la tecnología desempeña un papel cada vez más predominante, la integración de la IA en la educación básica ofrece una gama de oportunidades y desafíos. (22) Desde la personalización del aprendizaje hasta la optimización de la enseñanza, la IA busca revolucionar la forma en que se imparten y se adquieren conocimientos en las aulas de todo el mundo. (23) En ese orden de ideas, la presente investigación se centró en evaluar las perspectivas de los docentes sobre el rol que tiene la IA en el contexto educativo.…”
Section: Discussionunclassified
“…Selain itu, ICT memungkinkan pembelajaran jarak jauh, yang sangat penting dalam situasi pandemi atau ketika akses fisik ke sekolah terbatas. Selain sebagai media, ICT juga memfasilitasi model pembelajaran yang sesuai, seperti Blended Learning, di mana siswa dapat menggabungkan pembelajaran online dengan interaksi langsung dalam kelas, meningkatkan fleksibilitas dan personalisasi dalam proses pembelajaran [2], [3] . ICT juga memungkinkan pembelajaran mandiri dan pengembangan keterampilan mandiri, yang merupakan aspek penting dalam pendidikan modern [4].…”
Section: A Pendahuluanunclassified